Nexus between Christianity and Igbo tradition in marriage rites in Igboland, Nigeria - Okechukwu, Onyeiwu Henry (2023)
Marriage is not just a union between a man and a woman, but a tie between two families, and sometimes communities. Marriage is a legal union that is established through the fulfillment of certain requirements. Marriage and requirements for contracting marriage between two parties varies in different societies and cultures. This varies from community to community and even from country to country. In some communities, it is simple while in some others, it is complex. Generally speaking, in Igboland marriage is usually done traditionally and based on Christian marriage rites. However, some individuals choose to do both traditional marriage and Christian Marriage, or either of them, depending on which is more important to them. This has led to controversies in the entire Igboland as to which is more important, while some agree that the Igbo traditional marriage is more important, some believe that the Christian marriage is more important. Thus, this study focused on exploring the nexus between Christian marriage rites and Igbo traditional marriage rites, with a specific focus on Imo State. The aim of this is to understand the similarities that exist between the two, in the view of making contributions to the scholarship which proposes the merging of the two by identifying key similarities between Christian Marriage and Traditional Marriage. To achieve the objective of this study, a qualitative approach was used, and through semi-structured interviews and observation, data was collected from married people in Imo State. Symbolic Interactionist Theory was used to analyze the concept of marriage. The findings of the study showed that in Imo state, both Igbo traditional marriage and Christian Marriage are significant, however, the most critical aspect of both Christian Religion Marriage and Igbo Traditional Marriage is the payment of bride price, which is regarded as the main symbol of the establishment of a Marriage union between a man and a woman. Regardless of the preference of the families, either Christian Marriage or Traditional Marriage, the bride price must be paid before the man and woman can be regarded as married. Also, the majority of the respondents see Igbo-traditional marriage ceremony as an indigenous cultural heritage. On the other hand, the respondents noted that Christian Marriage was introduced by Western missionaries during the colonial period. It is hoped that the findings of this study will contribute to the literature of Marriage practice in Imo, and towards the Standardization of Marriage rites in Imo State with the view of harmonizing the religious and traditional aspects of marriage in Imo State.